Understanding Migration Aversion Using Elicited Counterfactual Choice Probabilities - Gizem Kosar; Tyler Ransom; Wilbert van der Klaauw (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper investigates how migration and location choice decisions depend on a large set of location characteristics, with particular focus on measuring the importance and nature of the non-monetary cost of moving. We employ a stated-preference approach to elicit respondents' choice probabilities for a set of hypothetical choice scenarios, using two waves from the NY Fed's Survey of Consumer Expectations. Our hypothetical choice methodology elicits choice probabilities from which we recover the distribution of individual-level preferences for location and mobility attributes without concerns about omitted variables and selection biases that hamper analyses based on observed mobility choices alone. We estimate substantial heterogeneity in the willingness-to-pay (WTP) for location characteristics, both across and within demographic groups. Our results also indicate evidence of sorting into current locations based on preferences for these attributes as well as a strong negative association between respondents' non-monetary moving costs and their moving expectations and actual mobility decisions.
Keywords: J61; R23; D84; 330; subjective probabilities; stated choice methodology; migration; location choice